2020
DOI: 10.3390/jcm9082435
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Manifestations and Complications of Pheochromocytomas and Paragangliomas

Abstract: Pheochromocytomas and paragangliomas (PPGLs) are rare neuro-endocrine tumors. The catecholamine surge causes paroxysmal or chronic secondary hypertension. PPGLs may present as hypertensive- or PPGL-crisis with severe life-threatening cardiac and cerebrovascular complications. PPGLs-induced cardiac manifestations have been reported with diagnoses as PPGLs-induced electrocardiogram (ECG) changes “mimicking acute myocardial infarction”, arrhythmias, myocarditis, acute coronary syndrome, dilated cardiomyopathy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 109 publications
(244 reference statements)
3
54
0
5
Order By: Relevance
“…The coronary angiogram showed nonobstructed coronary arteries. We noted that most of such patients had few significant coronary atherosclerosis in past reports[ 8 - 10 ]. Most reports suggested that cardiomyopathy, severe coronary vasospasm, myocarditis, and tachycardia caused by excessive release of catecholamines result in elevated cardiac troponin and reduced left ventricular systolic function[ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 73%
“…The coronary angiogram showed nonobstructed coronary arteries. We noted that most of such patients had few significant coronary atherosclerosis in past reports[ 8 - 10 ]. Most reports suggested that cardiomyopathy, severe coronary vasospasm, myocarditis, and tachycardia caused by excessive release of catecholamines result in elevated cardiac troponin and reduced left ventricular systolic function[ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 73%
“…Norepinephrine secreted by pheochromocytoma can cause structural and functional remodeling of the heart, such as left ventricular hypertrophy. Catecholamines, especially norepinephrine, can cause myocardial damage by increasing the oxygen consumption and apoptosis of cardiomyocytes and can further lead to left ventricular systolic dysfunction and dilated cardiomyopathy ( 14 , 15 ). Some factors can lead to an imbalance of the oxygen supply and demand, such as cardiotoxicity of catecholamines, increased muscle mass and coronary artery spasm, causing myocardial ischemic necrosis ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms include chest pain, psychiatric symptoms, hyperglycemia, constipation, and syncope. Uncommon presenting symptoms include Takotsubo syndrome ( 22-24 ), other life-threating cardiovascular events ( 25 ), and preeclampsia ( 26 ).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…However, patients using phenoxybenzamine less frequently had intraoperative systolic blood pressure above the target range and hemodynamic instability. The intravenous alpha-blocker phentolamine is preferred in emergency situations, such as PPGL-crisis, due to its quick onset ( 25 ). Calcium channel blockers (nifedipine or amlodipine) normally are used as an addition to alpha adrenergic receptor blocker if further blood pressure control is required or occasionally for patients not tolerating alpha-blockers ( 76 , 79 ).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation